2019
DOI: 10.3390/medsci7050067
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels as Lower Urinary Tract Sensory Targets

Abstract: Several members of the transient receptor potential (TRP) superfamily, including TRPV1, TRPV2, TRPV4, TRM4, TRPM8 and TRPA1, are expressed in the lower urinary tract (LUT), not only in neuronal fibers innervating the bladder and urethra, but also in the urothelial and muscular layers of the bladder and urethral walls. In the LUT, TRP channels are mainly involved in nociception and mechanosensory transduction. Animal studies have suggested the therapeutic potential of several TRP channels for the treatment of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 127 publications
(175 reference statements)
2
37
0
Order By: Relevance
“…Figure 1 summarizes the mostly interrelated functional roles of insulin and the InsR and the TRPV1 receptor at system, organ and cellular levels. Although the significance of modulation of TRPV1 receptor function in the therapeutic management of pain, inflammatory states and neurogenic dysfunction, such as overactive bladder is now well established [157], further studies are warranted to exploit the possible therapeutic value of the observations summarized in this review. InsRs expressed on PSNs play a significant role in the mechanisms of neurite outgrowth of cultured PSNs and axonal regeneration in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 summarizes the mostly interrelated functional roles of insulin and the InsR and the TRPV1 receptor at system, organ and cellular levels. Although the significance of modulation of TRPV1 receptor function in the therapeutic management of pain, inflammatory states and neurogenic dysfunction, such as overactive bladder is now well established [157], further studies are warranted to exploit the possible therapeutic value of the observations summarized in this review. InsRs expressed on PSNs play a significant role in the mechanisms of neurite outgrowth of cultured PSNs and axonal regeneration in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 is known to contribute to nociceptive responses evoked by endogenous and exogenous irritants (Oyama et al, 2017), including MGO itself (Bierhaus et al, 2012;Eberhardt et al, 2012). On the other hand, TRPV1 and TRPV4 are involved in bladder activity in response to mechanical or chemical stimulus (Andersson, 2019). We found that MGO induced a marked increase in TRPA1 expression, which may account for the bladder hyperreflexia.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, nonhyperglycemic obese patients may exhibit increased plasma MGO levels (Masania et al, 2016). TRP channels are widely expressed in lower urinary tract tissues and play a critical role in the normal micturition reflex (for review: Andersson, 2019). TRPA1 is known to contribute to nociceptive responses evoked by endogenous and exogenous irritants (Oyama et al, 2017), including MGO itself (Bierhaus et al, 2012;Eberhardt et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these functions may act upon neurons, but may also be executed through effects on other cell types that express TRPV1 or that modulate neuronal properties. For example, human leukocytes have been reported to express TRPV1 [30], as well as urothelial cells (reviewed by Andersson [31]). Ongoing efforts will help identify IPSE's mechanisms of effect on TRPV1-associated nociception and may contribute to development of IPSE as a novel analgesic.…”
Section: Discussionmentioning
confidence: 99%